Discovery or extinction of new scleroderma species in amazonia? - Baseia, Iuri Goulart; Silva, Bianca Denise Barbosa da; Ishikawa, Noemia Kazue; Soares, João V.C.; França, Isadora F.; Ushijima, Shuji; Maekawa, Nitaro; Martín, María Paz (PLoS ONE, 2016)
The Amazon Forest is a hotspot of biodiversity harboring an unknown number of undescribed taxa. Inventory studies are urgent, mainly in the areas most endangered by human activities such as extensive dam construction, where species could be in risk of extinction before being described and named. In 2015, intensive studies performed in a few locations in the Brazilian Amazon rainforest revealed three new species of the genus Scleroderma: S. anomalosporum, S. camassuense and S. duckei. The two first species were located in one of the many areas flooded by construction of hydroelectric dams throughout the Amazon; and the third in the Reserva Florestal Adolpho Ducke, a protected reverse by the INPA. The species were identified through morphology and molecular analyses of barcoding sequences (Internal Transcribed Spacer nrDNA). Scleroderma anomalosporum is characterized mainly by the smooth spores under LM in mature basidiomata (under SEM with small, unevenly distributed granules, a characteristic not observed in other species of the genus), the large size of the basidiomata, up to 120 mm diameter, and the stelliform dehiscence; S. camassuense mainly by the irregular to stellate dehiscence, the subreticulated spores and the bright sulfur-yellow colour, and Scleroderma duckei mainly by the verrucose exoperidium, stelliform dehiscence, and verrucose spores. Description, illustration and affinities with other species of the genus are provided. © 2016 Baseia et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Internal Transcribed Spacer; Dna, Fungal; Amazonas; Basidiomata; Dna Sequence; Fungal Structures; Fungus; Fungus Identification; Fungus Spore; Nonhuman; Scleroderma (fungus); Scleroderma Anomalosporum; Scleroderma Camassuense; Scleroderma Duckei; Species Extinction; Species Identification; Stellate Dehiscence; Stelliform Dehiscence; Verrucose Exoperidium; Animals; Basidiomycetes; Chemistry; Classification; Forest; Genetics; Isolation And Purification; Metabolism; Phylogeny; Animalss; Basidiomycota; Dna, Fungal; Forests; Phylogeny